2016
DOI: 10.1002/ppul.23532
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on cystic fibrosis and physical activity: Is there a difference compared to healthy individuals?

Abstract: While we found similar levels of physical activity measured by accelerometry in patients with CF compared to healthy controls in general, young school-aged children showed less engagement in strenuous activities than their healthy counterparts. As the reduced physical activity in young school children was not likely to be explained by the disease state, strenuous physical activity may be enhanced by advocating exercise and sport. Pediatr Pulmonol. 2016;51:1020-1030. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 49 publications
(148 reference statements)
3
34
1
Order By: Relevance
“…In agreement with some, 6,18,32 but not all, 10,12 previous studies, no significant difference was observed in the PAL of children with and without CF, although a considerably higher proportion of our CF population met recommended guidelines compared to previous research. 12 Given the numerous additional health benefits for patients with CF, 4-9 over and above the physiological and psychosocial benefits of regular PA identified in healthy children, 3 these findings highlight the need for strategies to increase PA in this population.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with some, 6,18,32 but not all, 10,12 previous studies, no significant difference was observed in the PAL of children with and without CF, although a considerably higher proportion of our CF population met recommended guidelines compared to previous research. 12 Given the numerous additional health benefits for patients with CF, 4-9 over and above the physiological and psychosocial benefits of regular PA identified in healthy children, 3 these findings highlight the need for strategies to increase PA in this population.…”
Section: Discussionsupporting
confidence: 92%
“…Evenson 15 cut-points to find that 6-17 year old children with CF engaged in significantly less MVPA and vigorous physical activity (VPA) but demonstrated higher total and light physical activity (TPA and LPA, respectively). Yet Jantzen et al 16 found similar PAL in CF patients across the age and intensity spectrum, but less engagement in strenuous activities for schoolaged children (6-13 years) compared to healthy controls. Interestingly, when extreme values were removed, no relationship was present between strenuous PA and percentage predicted FEV1.…”
Section: Utilisedmentioning
confidence: 95%
See 2 more Smart Citations
“…Others described no significant differences in PA to healthy peers [2,7,10]. Regarding pulmonary function, some authors reported that higher PA levels were associated with a slower rate of decline in FEV 1 , specifically in girls with CF [5,11].…”
Section: Introductionmentioning
confidence: 99%